Integrated silicon-carbon composite negative electrode material and preparation method thereof
By forming a porous carbon layer and a silicon-carbon composite layer with a uniform thickness on the carbon-based material, the existing silicon-carbon anode material stability and complicated process problems are solved, and higher batch stability and cycle performance are achieved.
Patent Information
- Application Number
- CN202411399684.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-09
AI Technical Summary
The batch stability of the existing vapor-deposited silicon-carbon anode materials is poor and need to be mixed with graphite, which adds the battery preparation process.
Using integrated silicon carbon composite negative materials, by forming a porous carbon layer with average thickness on the carbon -based material substrate, and distributed with a silicon carbon composite layer on its surface to cover the non -fixed carbon layer Craft control silicon content and layer thickness.
Improve the batch stability of the material, reduce the process, enhance the connection between materials and graphite, and improve the circulation performance.
Smart Images

Figure CN118919704B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery negative electrode materials, and in particular to an integrated silicon-carbon composite negative electrode material and a preparation method thereof. Background Art
[0002] At present, the silicon negative electrode material industry is generally optimistic about the vapor deposition of silicon carbon, which has the advantages of high specific capacity, high initial efficiency, and smaller expansion than silicon oxygen negative electrode. At the same time, this material has a large cost reduction space in the future. At present, the vapor deposition of silicon carbon route of most manufacturers chooses activated porous carbon precursors for silicon deposition. The porous carbon precursors are mainly biomass, resin, petroleum coke, etc.
[0003] However, there are still some problems with the above materials. First, at present, porous carbon precursors are mainly activated by water, carbon dioxide, alkali and other methods. There is solid-solid, solid-gas, and solid-liquid contact during the activation process, which makes it difficult to ensure the uniform stability of porous carbon, and ultimately leads to poor batch stability of silicon-carbon negative electrode materials. Second, at present, most of the vapor-deposited silicon carbon is deposited using porous substrates. For particles with larger diameters, D50 is often greater than 5 μm or even more than 15 μm. It is difficult for silicon-containing gases to penetrate into the particles to form uniform deposition; and due to the small diameter of the porous matrix of small particles, saturation has been reached when the large particles are not deposited saturated, resulting in floating silicon on the surface of small particles, and poor stability during the deposition process, which ultimately leads to poor batch stability of silicon-carbon negative electrode materials. Third, downstream battery factories still need to mix and compound vapor-deposited silicon carbon with graphite in applications, which increases the battery preparation process. It is necessary to provide a carbon-silicon negative electrode material that can compound vapor-deposited silicon carbon with graphite to save practical application processes and improve the uniformity of the slurry. Summary of the invention
[0004] The purpose of the present invention is: on the one hand, to provide an integrated silicon-carbon composite negative electrode material having a silicon-carbon composite layer of uniform thickness and reducing surface floating silicon; on the other hand, to provide a method for preparing the aforementioned integrated silicon-carbon negative electrode material.
[0005] The integrated silicon-carbon composite negative electrode material provided by the present invention comprises:
[0006] The matrix of the carbon-based material,
[0007] a silicon-carbon composite layer distributed on the surface of the substrate, and
[0008] an amorphous carbon layer coated on the surface of the silicon-carbon composite layer;
[0009] Among them, the silicon-carbon composite layer includes a porous carbon layer with a thickness of 0.01-4 μm, and a silicon element distributed in the micropores of the porous carbon layer; the total silicon content in the integrated silicon-carbon composite negative electrode material is less than 15 wt%, and the porous carbon layer is based on a carbon-based material, and a silicon carbide layer is obtained by vapor deposition, and then the silicon carbide layer is formed by heat treatment using a halogen gas.
[0010] Furthermore, the carbon-based material is selected from graphite and / or mesophase carbon microspheres. The graphite is natural graphite or artificial graphite or a combination of the two in any proportion. The graphite is trigonal graphite or hexagonal graphite or a combination of the two in any proportion.
[0011] Furthermore, the D50 of the matrix is 5-25 μm. For natural graphite or artificial graphite, the preferred D50 is 5-25 μm. For mesophase microspheres, the preferred D50 is 5-25 μm.
[0012] The present invention is to use the silicon lattice of silicon carbide to generate a porous carbon layer with uniform pores and a thickness of 0.01-4 μm on a carbon-based material substrate. It is particularly noteworthy that once the thickness of the porous carbon layer exceeds 4 μm, the gaseous silicon source in the deposition process is not easy to enter the interior of the porous carbon layer, resulting in floating silicon on the surface. For this reason, the porous carbon layer is more preferably 0.01-2 μm thick. At the same time, if an excessive amount of silicon is deposited in the chemical deposition process, the mass of silicon in the silicon-carbon composite layer exceeds 65 wt%, which is also likely to cause floating silicon to form on the surface of the porous carbon layer. The surface floating silicon expands greatly during the subsequent cycle process, resulting in poor subsequent cycle performance. The silicon content in the silicon-carbon composite layer of the present invention is 0-65 wt%, preferably 30-50 wt%. More preferably, the silicon content in the silicon-carbon composite layer can be selected as 35 wt%, 40 wt%, and 45 wt%. Furthermore, the total silicon content in the integrated silicon-carbon composite negative electrode material of the present invention is less than 15 wt%, thereby avoiding the serious expansion of the pole piece and the reduction of cycle performance due to excessive silicon content during actual application. The present invention greatly reduces the distance (<4μm) required for the vapor silicon source to penetrate into the interior through the composite of the silicon-carbon composite layer and the carbon-based material matrix, and the thickness of the silicon-carbon composite layer of the carbon-based material matrix of different sizes is close, so the state consistency of different particles during the vapor silicon source deposition process is high, and the batch stability of the material is high.
[0013] The pores of the porous carbon layer of the present invention are substantially derived from the silicon lattice of silicon carbide and are formed after heat treatment with halogen gas, so that the porous carbon layer has pores with an average pore diameter of 0.3-2 nm.
[0014] Furthermore, the thickness of the amorphous carbon layer is 0-500 nm, preferably between 10-100 nm.
[0015] The method for preparing the integrated silicon-carbon composite negative electrode material provided by the present invention specifically comprises:
[0016] (1) Using a carbon-based material as a substrate, a silicon carbide layer with a thickness of 0.01-4 μm is obtained by first vapor deposition;
[0017] (2) heat treating the silicon carbide layer using a halogen gas to form a porous carbon layer;
[0018] (3) obtaining a silicon-carbon composite layer by a second vapor deposition;
[0019] (4) Introducing carbon source gas for carbon coating.
[0020] The method provided by the present invention is based on carbon-based materials as a matrix, rather than directly using porous carbon as a matrix. The maximum distance of actual silicon deposition is the thickness of the porous carbon layer. This design ensures the stability of the material batch. In order to obtain a porous carbon layer with high thickness consistency, the present invention first uses the first vapor deposition to form a silicon carbide layer with high thickness consistency, which is converted into a porous carbon layer through halogen gas and heat treatment. The pores of the porous carbon layer come from the silicon lattice of silicon carbide, which has higher stability and uniformity than the traditional porous carbon activation process. In addition, the pores of the porous carbon layer based on the silicon lattice of silicon carbide can be more efficiently deposited by the second vapor deposition, so that amorphous silicon is deposited inside the hole. The integrated material prepared by this method has a certain bonding at the interface between porous carbon and graphite, which is conducive to the connection of the silicon-carbon negative electrode with the graphite surface during the expansion process without falling off.
[0021] It is worth noting that the thickness of the silicon carbide layer described in step (1) of the present application corresponds to the thickness of the porous carbon layer described in step (2). For example, the silicon carbide layer having a thickness of 0.01-4 μm obtained by the first vapor deposition can also be understood as the porous carbon layer formed by heat treating the silicon carbide layer with halogen gas also having a thickness of 0.01-4 μm.
[0022] The carbon-based material is selected from any one or more combinations of natural graphite, artificial graphite, and mesophase carbon microspheres, and the D50 of the matrix is 5-25 μm.
[0023] Furthermore, the porous carbon layer has pores of 0.3-2 nm. The pores are formed by heat treating SiC with halogen gas. In this way, a porous carbon layer with uniform thickness can be stably obtained for depositing amorphous silicon in the second vapor deposition.
[0024] Further, the first vapor deposition includes introducing a first gaseous silicon source at a temperature of 800-1600°C; the first gaseous silicon source is a carbon-containing silicon source, including but not limited to any one or more combinations of trichloromethylsilane, dichlorodimethylsilane, tetraethoxysilane, and methyltriethoxysilane. Among them, the preferred first vapor deposition temperature is 900-1400°C, and the more preferred first vapor deposition temperature is 1000-1200°C.
[0025] The halogen gas in step (2) includes but is not limited to any one or more combinations of F2, Cl2, Br2, I2, and can also be a halogen gas containing two different elements at the same time, which is mainly used to chemically etch the surface of silicon carbide under high temperature treatment. Among them, the inventors found that a treatment temperature of 600-1500 ° C can ensure that the obtained porous carbon layer has the desired pore size, for example, a porous carbon layer with an average pore size of 0.3-2 nm is obtained. The preferred treatment temperature is 700-1200 ° C, and the more preferred treatment temperature is 800-1000 ° C. However, if the treatment temperature is too high, for example, exceeding 2000 ° C, the average pore size of the porous carbon layer will be less than 0.3 nm, which will be detrimental to the deposition of silane gas, and ultimately cause the silicon content of the product to fail to meet expectations.
[0026] The second vapor deposition includes introducing a second gaseous silicon source at a temperature of 400-800°C; the second gaseous silicon source is a carbon-free silicon source, more specifically, the second gaseous silicon source includes but is not limited to any one or more combinations of monosilane, disilane, and trichlorosilane. For the carbon-free silicon source, the preferred second vapor deposition temperature is controlled at 500-700°C, and the more preferred second vapor deposition temperature is 600-650°C, which is conducive to the formation of amorphous carbon.
[0027] It is worth noting that the second vapor deposition of the present invention can be carried out in an environment of 1KPa-100KPa (or normal atmospheric pressure), preferably in an environment of 1KPa-50KPa, and more preferably in an environment of 1KPa-3KPa. In a low-pressure environment, the vapor silicon source can be more efficiently deposited into the porous carbon layer to avoid the formation of floating silicon on the surface.
[0028] Furthermore, the step (4) is to perform a third vapor deposition on the silicon-carbon composite layer using a carbon source gas, wherein the carbon source gas is any one or more of acetylene, methane, ethylene, and benzene. The temperature of the third vapor deposition is 500-1000°C.
[0029] The integrated silicon-carbon composite negative electrode material prepared by the above method has a substrate made of carbon-based material, a silicon-carbon composite layer distributed on the surface of the substrate, and an amorphous carbon layer coated on the surface of the silicon-carbon composite layer. Among them, the silicon-carbon composite layer is first obtained by the first vapor deposition to obtain a silicon carbide layer, and then a halogen gas is introduced for heat treatment to form a porous carbon layer, which solves the problem of uneven activation and insufficient stability in the traditional porous carbon preparation process; and then a carbon-free silane gas is introduced for the second vapor deposition, and the amount of silane introduced in this step is controlled so that the total silicon content in the integrated silicon-carbon composite negative electrode material is less than 15 wt%, thereby avoiding the serious expansion of the pole piece due to excessive silicon content in actual applications, and the cycle performance is reduced. In the process of generating the silicon carbide layer, it is beneficial to the bonding of the porous carbon layer and the substrate, improve the stability of the material structure, and the integrated design preferably using graphite as the substrate brings new ideas to the production of battery pole pieces, replacing the compounding process in actual production. The integrated silicon-carbon composite process provided by the present invention provides a porous carbon layer with uniform thickness (<4 um), which greatly reduces the distance required for silicon-containing gas to penetrate into the interior for deposition, improves the consistency of different particle states during silicon-containing gas deposition, and ultimately improves material batch stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a schematic diagram of the preparation process route of the integrated silicon-carbon composite negative electrode material of the present application.
[0031] Figure 2 This is a transmission electron microscope image of the carbon coating layer of the integrated silicon-carbon composite negative electrode material of Example 1 of the present application. DETAILED DESCRIPTION
[0032] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0033] Example 1
[0034] This embodiment provides an integrated silicon-carbon composite negative electrode material, and its preparation process is as follows: Figure 1 As shown, the specific preparation method is as follows:
[0035] 1) A natural graphite anode with a D50 of 10 μm was selected as the substrate, and a SiC layer was deposited on its surface using trichloromethylsilane. The deposition temperature was 1000 °C and the thickness of the SiC layer was 0.5 μm.
[0036] 2) The precursor obtained in step 1) is heat treated in a chlorine atmosphere at a temperature of 950° C. to obtain a porous carbon layer.
[0037] 3) The intermediate particles obtained in step 2) are subjected to silicon deposition in a rotary furnace, the silicon source is silane gas, the deposition temperature is 550° C., and the deposition pressure is 1000 Pa.
[0038] 4) The intermediate product particles obtained in step 3) are subjected to CVD carbon coating in a rotary furnace, the carbon source is acetylene gas, the deposition temperature is 600°C, and the thickness of the carbon coating layer is 21nm. The total silicon content in the silicon-carbon composite negative electrode material prepared by the above process is 8.2 wt%, wherein the silicon content in the silicon-carbon composite layer is 30-50 wt%.
[0039] In this embodiment, the above material properties are confirmed by the following detection methods respectively. Unless otherwise specified, the following embodiments are based on the detection methods mentioned in this embodiment.
[0040] The thickness of the SiC layer in step 1) is obtained by electron microscopy and EDS observation.
[0041] In step 4), the thickness of the carbon coating layer was observed by transmission electron microscopy, and the results are as follows: Figure 2 shown.
[0042] The total silicon mass percentage in step 4) is tested according to the method in GB / T 38823-2020.
[0043] Example 2
[0044] This embodiment provides an integrated silicon-carbon composite negative electrode material, and its preparation process is as follows: Figure 1 As shown, the specific preparation method is as follows:
[0045] 1) A natural graphite negative electrode with a D50 of 10 μm was selected as the substrate, and a SiC layer was deposited on its surface using trichloromethylsilane. The deposition temperature was 1000 °C and the thickness of the SiC layer was 0.9 μm.
[0046] 2) The precursor obtained in step 1) is heat treated in a chlorine atmosphere at a temperature of 950° C. to obtain a porous carbon layer.
[0047] 3) The intermediate particles obtained in step 2) are subjected to silicon deposition in a rotary furnace, the silicon source is silane gas, the deposition temperature is 550° C., and the deposition pressure is 1000 Pa.
[0048] 4) The intermediate product particles obtained in step 3) are subjected to CVD carbon coating in a rotary furnace, the carbon source is acetylene gas, the deposition temperature is 600°C, and the thickness of the carbon coating layer is 20nm. The total silicon content in the silicon-carbon composite negative electrode material prepared by the above process is 8.4 wt%.
[0049] Example 3
[0050] This embodiment provides an integrated silicon-carbon composite negative electrode material, and its preparation process is as follows: Figure 1 As shown, the specific preparation method is as follows:
[0051] 1) Select D50=10μm natural graphite negative electrode as the substrate, and use trichloromethylsilane to deposit a SiC layer on its surface. The deposition temperature is 1000℃ and the thickness of the SiC layer is 1.0μm.
[0052] 2) The precursor obtained in step 1) is heat treated in a chlorine atmosphere at a temperature of 950° C. to obtain a porous carbon layer.
[0053] 3) The intermediate particles obtained in step 2) are subjected to silicon deposition in a rotary furnace, the silicon source is silane gas, the deposition temperature is 550° C., and the deposition pressure is 1000 Pa.
[0054] 4) The intermediate product particles obtained in step 3) are subjected to CVD carbon coating in a rotary furnace, the carbon source is acetylene gas, the deposition temperature is 600°C, and the thickness of the carbon coating layer is 17nm. The total silicon content in the silicon-carbon composite negative electrode material prepared by the above process is 14.8 wt%.
[0055] Example 4
[0056] This embodiment provides an integrated silicon-carbon composite negative electrode material, and its preparation process is as follows: Figure 1 As shown, the specific preparation method is as follows:
[0057] 1) Select D50=10μm natural graphite negative electrode as the substrate, and use trichloromethylsilane to deposit a SiC layer on its surface. The deposition temperature is 1000℃ and the thickness of the SiC layer is 0.5μm.
[0058] 2) The precursor obtained in step 1) is heat treated in a chlorine atmosphere at a temperature of 950° C. to obtain a porous carbon layer.
[0059] 3) The intermediate particles obtained in step 2) are subjected to silicon deposition in a rotary furnace, the silicon source is silane gas, the deposition temperature is 550° C., and the deposition pressure is 1000 Pa.
[0060] 4) The intermediate product particles obtained in step 3) are subjected to CVD carbon coating in a rotary furnace, the carbon source is acetylene gas, the deposition temperature is 600°C, and the thickness of the carbon coating layer is 20nm. The total silicon content in the silicon-carbon composite negative electrode material prepared by the above process is 5.3 wt%.
[0061] Example 5
[0062] This embodiment provides an integrated silicon-carbon composite negative electrode material, and its preparation process is as follows: Figure 1 As shown, the specific preparation method is as follows:
[0063] 1) Select D50=10μm natural graphite negative electrode as the substrate, and use trichloromethylsilane to deposit a SiC layer on its surface. The deposition temperature is 1000℃ and the thickness of the SiC layer is 1μm.
[0064] 2) The precursor obtained in step 1) is heat treated in a chlorine atmosphere at a temperature of 950° C. to obtain a porous carbon layer.
[0065] 3) The intermediate particles obtained in step 2) are subjected to silicon deposition in a rotary furnace, the silicon source is silane gas, the deposition temperature is 550° C., and the deposition pressure is 1000 Pa.
[0066] 4) The intermediate product particles obtained in step 3) are subjected to CVD carbon coating in a rotary furnace, the carbon source is acetylene gas, the deposition temperature is 600°C, and the thickness of the carbon coating layer is 97nm. The total silicon content in the silicon-carbon composite negative electrode material prepared by the above process is 8.6 wt%.
[0067] Example 6
[0068] This embodiment provides an integrated silicon-carbon composite negative electrode material, and its preparation process is as follows: Figure 1 As shown, the specific preparation method is as follows:
[0069] 1) A natural graphite negative electrode with a D50 of 15 μm was selected as the substrate, and a SiC layer was deposited on its surface using trichloromethylsilane. The deposition temperature was 1000 °C and the thickness of the SiC layer was 1.3 μm.
[0070] 2) The precursor obtained in step 1) is heat treated in a chlorine atmosphere at a temperature of 950° C. to obtain a porous carbon layer.
[0071] 3) The intermediate particles obtained in step 2) are subjected to silicon deposition in a rotary furnace, the silicon source is silane gas, the deposition temperature is 550° C., and the deposition pressure is 1000 Pa.
[0072] 4) The intermediate product particles obtained in step 3) are subjected to CVD carbon coating in a rotary furnace, the carbon source is acetylene gas, the deposition temperature is 600°C, and the thickness of the carbon coating layer is 16nm. The total silicon content in the silicon-carbon composite negative electrode material prepared by the above process is 8.3 wt%.
[0073] Example 7
[0074] This embodiment provides an integrated silicon-carbon composite negative electrode material, and its preparation process is as follows: Figure 1 As shown, the specific preparation method is as follows:
[0075] 1) Select D50=10μm natural graphite negative electrode as the substrate, and use trichloromethylsilane to deposit a SiC layer on its surface. The deposition temperature is 1000℃ and the thickness of the SiC layer is 0.5μm.
[0076] 2) The precursor obtained in step 1) is heat treated in a chlorine atmosphere at a temperature of 950° C. to obtain a porous carbon layer.
[0077] 3) The intermediate particles obtained in step 2) are subjected to silicon deposition in a rotary furnace, the silicon source is silane gas, the deposition temperature is 550° C., and the deposition pressure is 3000 Pa.
[0078] 4) The intermediate product particles obtained in step 3) are subjected to CVD carbon coating in a rotary furnace, the carbon source is acetylene gas, the deposition temperature is 600°C, and the thickness of the carbon coating layer is 19nm. The total silicon content in the silicon-carbon composite negative electrode material prepared by the above process is 7.9 wt%.
[0079] Example 8
[0080] This embodiment provides an integrated silicon-carbon composite negative electrode material, and its preparation process is as follows: Figure 1 As shown, the specific preparation method is as follows:
[0081] 1) An artificial graphite anode with a D50 of 10 μm was selected as the substrate, and a SiC layer was deposited on its surface using trichloromethylsilane. The deposition temperature was 1000 °C and the thickness of the SiC layer was 0.5 μm.
[0082] 2) The precursor obtained in step 1) is heat treated in a chlorine atmosphere at a temperature of 950° C. to obtain a porous carbon layer.
[0083] 3) The intermediate particles obtained in step 2) are subjected to silicon deposition in a rotary furnace, the silicon source is silane gas, the deposition temperature is 550° C., and the deposition pressure is 1000 Pa.
[0084] 4) The intermediate product particles obtained in step 3) are subjected to CVD carbon coating in a rotary furnace, the carbon source is acetylene gas, the deposition temperature is 600°C, and the thickness of the carbon coating layer is 21nm. The total silicon content in the silicon-carbon composite negative electrode material prepared by the above process is 8.2 wt%.
[0085] Example 9
[0086] This embodiment provides an integrated silicon-carbon composite negative electrode material, and its preparation process is as follows: Figure 1 As shown, the specific preparation method is as follows:
[0087] 1) Select D50=10μm natural graphite negative electrode as the substrate, and use trichloromethylsilane to deposit a SiC layer on its surface. The deposition temperature is 1000℃ and the thickness of the SiC layer is 0.5μm.
[0088] 2) The precursor obtained in step 1) is heat treated in a chlorine atmosphere at a temperature of 700° C. to obtain a porous carbon layer.
[0089] 3) The intermediate particles obtained in step 2) are subjected to silicon deposition in a rotary furnace, the silicon source is silane gas, the deposition temperature is 550° C., and the deposition pressure is 1000 Pa.
[0090] 4) The intermediate product particles obtained in step 3) are subjected to CVD carbon coating in a rotary furnace, the carbon source is acetylene gas, the deposition temperature is 600°C, and the thickness of the carbon coating layer is 22nm. The total silicon content in the silicon-carbon composite negative electrode material prepared by the above process is 8.0 wt%.
[0091] Example 10
[0092] This embodiment provides an integrated silicon-carbon composite negative electrode material, and its preparation process is as follows: Figure 1 As shown, the specific preparation method is as follows:
[0093] 1) Select D50=10μm natural graphite negative electrode as the substrate, and use trichloromethylsilane to deposit a SiC layer on its surface. The deposition temperature is 1000℃ and the thickness of the SiC layer is 0.5μm.
[0094] 2) The precursor obtained in step 1) is heat treated in a chlorine atmosphere at a temperature of 950° C. to obtain a porous carbon layer.
[0095] 3) The intermediate particles obtained in step 2) are subjected to silicon deposition in a rotary furnace, the silicon source is silane gas, the deposition temperature is 550° C., and the deposition pressure is 1000 Pa.
[0096] 4) The intermediate product particles obtained in step 3) are subjected to CVD carbon coating in a rotary furnace, the carbon source is acetylene gas, the deposition temperature is 650°C, and the thickness of the carbon coating layer is 47nm. The total silicon content in the silicon-carbon composite negative electrode material prepared by the above process is 8.3 wt%.
[0097] Embodiment 11
[0098] This embodiment provides an integrated silicon-carbon composite negative electrode material, and its preparation process is as follows: Figure 1 As shown, the specific preparation method is as follows:
[0099] 1) Select D50=10μm mesophase carbon microspheres as the negative electrode substrate, and use trichloromethylsilane to deposit a SiC layer on its surface. The deposition temperature is 1000℃ and the thickness of the SiC layer is 0.5μm.
[0100] 2) The precursor obtained in step 1) is heat treated in a chlorine atmosphere at a temperature of 700° C. to obtain a porous carbon layer.
[0101] 3) The intermediate particles obtained in step 2) are subjected to silicon deposition in a rotary furnace, the silicon source is silane gas, the deposition temperature is 550° C., and the deposition pressure is 1000 Pa.
[0102] 4) The intermediate product particles obtained in step 3) are subjected to CVD carbon coating in a rotary furnace, the carbon source is acetylene gas, the deposition temperature is 600°C, and the thickness of the carbon coating layer is 20nm. The total silicon content in the silicon-carbon composite negative electrode material prepared by the above process is 8.5 wt%.
[0103] Example 12
[0104] This embodiment provides an integrated silicon-carbon composite negative electrode material, and its preparation process is as follows: Figure 1 As shown, the specific preparation method is as follows:
[0105] 1) Select D50=10μm mesophase carbon microspheres as the negative electrode substrate, and use dichlorodimethylsilane to deposit a SiC layer on its surface. The deposition temperature is 1000℃ and the thickness of the SiC layer is 0.5μm.
[0106] 2) The precursor obtained in step 1) is heat treated in a chlorine atmosphere at a temperature of 700° C. to obtain a porous carbon layer.
[0107] 3) The intermediate particles obtained in step 2) are subjected to silicon deposition in a rotary furnace, the silicon source is silane gas, the deposition temperature is 550° C., and the deposition pressure is 1000 Pa.
[0108] 4) The intermediate product particles obtained in step 3) are subjected to CVD carbon coating in a rotary furnace, the carbon source is acetylene gas, the deposition temperature is 600°C, and the thickness of the carbon coating layer is 19nm. The total silicon content in the silicon-carbon composite negative electrode material prepared by the above process is 13.0 wt%.
[0109] Comparative Example 1
[0110] The integrated silicon-carbon composite negative electrode material is prepared by the following method:
[0111] 1) A natural graphite anode with a D50 of 10 μm was selected as the substrate, and a SiC layer was deposited on its surface using trichloromethylsilane. The deposition temperature was 1000 °C and the thickness of the SiC layer was 0.5 μm.
[0112] 2) The precursor obtained in step 1) is heat treated in a chlorine atmosphere at a temperature of 950° C. to obtain a porous carbon layer.
[0113] 3) The intermediate particles obtained in step 2) are subjected to silicon deposition in a rotary furnace, the silicon source is silane gas, the deposition temperature is 550° C., and the deposition pressure is normal pressure.
[0114] 4) The intermediate product particles obtained in step 3) are subjected to CVD carbon coating in a rotary furnace, the carbon source is acetylene gas, the deposition temperature is 600°C, and the thickness of the carbon coating layer is 17nm. The total silicon content in the silicon-carbon composite negative electrode material prepared by the above process is 7.0 wt%.
[0115] Comparative Example 2
[0116] The integrated silicon-carbon composite negative electrode material is prepared by the following method:
[0117] 1) A natural graphite anode with a D50 of 10 μm was selected as the substrate, and a SiC layer was deposited on its surface using trichloromethylsilane. The deposition temperature was 1000 °C and the thickness of the SiC layer was 5 μm.
[0118] 2) The precursor obtained in step 1) is heat treated in a chlorine atmosphere at a temperature of 950° C. to obtain a porous carbon layer.
[0119] 3) The intermediate particles obtained in step 2) are subjected to silicon deposition in a rotary furnace, the silicon source is silane gas, the deposition temperature is 550° C., and the deposition pressure is 1000 Pa.
[0120] 4) The intermediate product particles obtained in step 3) are subjected to CVD carbon coating in a rotary furnace, the carbon source is acetylene gas, the deposition temperature is 600°C, and the thickness of the carbon coating layer is 15nm. The total silicon content in the silicon-carbon composite negative electrode material prepared by this process is 8.1 wt%.
[0121] Comparative Example 3
[0122] The integrated silicon-carbon composite negative electrode material is prepared by the following method:
[0123] 1) A natural graphite anode with a D50 of 10 μm was selected as the substrate, and a SiC layer was deposited on its surface using trichloromethylsilane. The deposition temperature was 1000 °C and the thickness of the SiC layer was 0.5 μm.
[0124] 2) The precursor obtained in step 1) is heat treated in a chlorine atmosphere at a temperature of 950° C. to obtain a porous carbon layer.
[0125] 3) The intermediate particles obtained in step 2) are subjected to silicon deposition in a rotary furnace, the silicon source is silane gas, the deposition temperature is 550° C., and the deposition pressure is 1000 Pa.
[0126] 4) The intermediate product particles obtained in step 3) are subjected to CVD carbon coating in a rotary furnace, the carbon source is acetylene gas, the deposition temperature is 600°C, and the thickness of the carbon coating layer is 24nm. The total silicon content in the silicon-carbon composite negative electrode material prepared by this process is 19 wt%.
[0127] Comparative Example 4
[0128] The integrated silicon-carbon composite negative electrode material is prepared by the following method:
[0129] 1) A natural graphite anode with a D50 of 10 μm was selected as the substrate, and a SiC layer was deposited on its surface using trichloromethylsilane. The deposition temperature was 1000 °C and the thickness of the SiC layer was 0.5 μm.
[0130] 2) The precursor obtained in step 1) is heat treated in a chlorine atmosphere at a temperature of 2400° C. to obtain a porous carbon layer. The average pore size of the porous carbon layer obtained by the high temperature treatment is less than 0.3 nm.
[0131] 3) The intermediate particles obtained in step 2) are subjected to silicon deposition in a rotary furnace, the silicon source is silane gas, the deposition temperature is 550° C., and the deposition pressure is 1000 Pa.
[0132] 4) The intermediate product particles obtained in step 3) are subjected to CVD carbon coating in a rotary furnace, the carbon source is acetylene gas, the deposition temperature is 600°C, and the thickness of the carbon coating layer is 20nm. The total silicon content in the silicon-carbon composite negative electrode material prepared by this process is 7.5 wt%.
[0133] Comparative Example 5
[0134] The integrated silicon-carbon composite negative electrode material is prepared by the following method:
[0135] 1) A natural graphite anode with a D50 of 10 μm was selected as the substrate, and a SiC layer was deposited on its surface using trichloromethylsilane. The deposition temperature was 1000 °C and the thickness of the SiC layer was 0.5 μm.
[0136] 2) The precursor obtained in step 1) is heat treated in a chlorine atmosphere at a temperature of 950° C. to obtain a porous carbon layer.
[0137] 3) The intermediate particles obtained in step 2) are subjected to silicon deposition in a rotary furnace, the silicon source is silane gas, the deposition temperature is 1000° C., and the deposition pressure is 1000 Pa. The deposition temperature is too high, resulting in the formation of SiC.
[0138] 4) The intermediate product particles obtained in step 3) are subjected to CVD carbon coating in a rotary furnace, the carbon source is acetylene gas, the deposition temperature is 600°C, and the thickness of the carbon coating layer is 22nm. The total silicon content in the silicon-carbon composite negative electrode material prepared by this process is 8.7 wt%.
[0139] The silicon-carbon composite negative electrode materials provided in the above embodiments and comparative examples were produced according to the same preparation process to obtain button batteries, and the test results are shown in Table 1. Taking Example 1 as an example, the silicon-carbon composite negative electrode material, carboxymethyl cellulose, and Super P were weighed at a mass ratio of 90:5:5, and an appropriate amount of deionized water was added and then ball-milled for 2 hours using a planetary ball mill. The ball-milled slurry was coated on the current collector, and after vacuum drying at 80°C for 12 hours, it was cut into negative electrode sheets with a diameter of 12 mm. Metal lithium was used as the counter electrode and reference electrode, and the electrolyte used a concentration of 1 mol / L LiPF6, and the solvent was a mixed solution of diethyl carbonate and ethylene carbonate (volume ratio of 1:1). The button batteries were assembled in a glove box with an argon atmosphere.
[0140] Table 1 Electrochemical performance of examples and comparative examples
[0141] Capacity (mAh / g) First effect (%) Cycle (200 times, %) Example 1 565 90.3 69.5 Example 2 560 90.2 70.7 Example 3 752 91.9 61 Example 4 468 87.9 71.2 Example 5 493 89.6 71.7 Example 6 572 90.0 67.4 Example 7 545 89.6 68.4 Example 8 558 91.5 70.0 Example 9 556 86.6 69.4 Example 10 528 90.7 71.5 Embodiment 11 526 87.8 70.9 Example 12 624 90.6 65 Comparative Example 1 528 89.8 60.4 Comparative Example 2 541 85.9 62.1 Comparative Example 3 848 91.4 47.5 Comparative Example 4 544 81.4 43.7 Comparative Example 5 298 84.2 70.7
[0142] From the above embodiments and comparative examples, it can be obtained that the higher the total silicon content, the higher the capacity and first efficiency, but the cycle performance deteriorates, especially when the total silicon content is greater than 15 wt%, the cycle performance deteriorates seriously; under the same silicon content, the thicker the SiC layer, the better the cycle performance, but the first efficiency and capacity decrease.
[0143] From the production process point of view, during silicon deposition, the low-pressure environment can deposit more silicon, and the less floating silicon on the surface improves the cycle performance. The temperature of the two vapor depositions also has an important impact on product quality. The first vapor deposition is used to generate silicon carbide, while the second vapor deposition is to obtain amorphous silicon (avoiding the formation of silicon carbide). Randomly changing the temperature will lead to reduced silicon deposition and affect the capacity.
[0144] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An integrated silicon-carbon composite negative electrode material, characterized in that: The silicon-carbon composite negative electrode material comprises: The matrix of carbon-based materials, a silicon-carbon composite layer distributed on the surface of the substrate, and an amorphous carbon layer coated on the surface of the silicon-carbon composite layer; The silicon-carbon composite layer comprises a porous carbon layer with a thickness of 0.01-4 μm, and silicon single substance distributed in the micropores of the porous carbon layer; the total silicon content in the integrated silicon-carbon composite negative electrode material is less than 15wt%; The porous carbon layer is formed by using a carbon-based material as a matrix, obtaining a silicon carbide layer by vapor deposition, and then heat-treating the silicon carbide layer at 600-1500° C. using a halogen gas; the carbon-based material is selected from one or more of natural graphite, artificial graphite, and mesophase carbon microspheres.
2. The integrated silicon-carbon composite negative electrode material according to claim 1, characterized in that: The D50 of the substrate is 5-25 μm.
3. An integrated silicon-carbon composite negative electrode material according to claim 1 or 2, characterized in that: The porous carbon layer has pores with an average pore diameter of 0.3-2 nm.
4. The integrated silicon-carbon composite negative electrode material according to claim 1 or 2, characterized in that: The thickness of the silicon-carbon composite layer is 0.01-2 μm, and the silicon content is 0-65 wt %, wherein the silicon content is not zero.
5. The integrated silicon-carbon composite negative electrode material according to claim 1 or 2, characterized in that: The thickness of the amorphous carbon layer is 0-500 nm, wherein the thickness of the amorphous carbon layer is not zero.
6. A method for preparing the integrated silicon-carbon composite negative electrode material according to claim 1 or 2, characterized in that: The method comprises the following preparation steps: (1) Using a carbon-based material as a substrate, a silicon carbide layer with a thickness of 0.01-4 μm is obtained by first vapor deposition; (2) heat treating the silicon carbide layer using a halogen gas to form a porous carbon layer; (3) obtaining a silicon-carbon composite layer at a temperature of 400-800°C by a second vapor deposition; (4) Introducing carbon source gas for carbon coating.
7. The method for preparing an integrated silicon-carbon composite negative electrode material according to claim 6, characterized in that: The carbon-based material is selected from one or more of natural graphite, artificial graphite, and mesophase carbon microspheres.
8. The method for preparing an integrated silicon-carbon composite negative electrode material according to claim 7, characterized in that: The D50 of the substrate is 5-25 μm.
9. The method for preparing an integrated silicon-carbon composite negative electrode material according to claim 7 or 8, characterized in that: The porous carbon layer has pores of 0.3-2 nm.
10. The method for preparing an integrated silicon-carbon composite negative electrode material according to claim 6, characterized in that: The first vapor deposition comprises introducing a first gaseous silicon source at a temperature of 800-1600° C.; the first gaseous silicon source comprises any one or more combinations of trichloromethylsilane, dichlorodimethylsilane, tetraethoxysilane, and methyltriethoxysilane.
11. The method for preparing an integrated silicon-carbon composite negative electrode material according to claim 7, characterized in that: The halogen gas in step (2) is any one or more of F2, Cl2, Br2, and I2, and the treatment temperature is 600-1500°C.
12. The method for preparing an integrated silicon-carbon composite negative electrode material according to claim 7, characterized in that: The second vapor deposition comprises introducing a second gaseous silicon source at a temperature of 400-800° C.; the second gaseous silicon source comprises any one or more combinations of monosilane, disilane and trichlorosilane.
13. The method for preparing an integrated silicon-carbon composite negative electrode material according to claim 12, characterized in that: The second vapor deposition is performed in an environment of 1 KPa-100 KPa.
14. The method for preparing an integrated silicon-carbon composite negative electrode material according to claim 6, characterized in that: The step (4) is to perform a third vapor deposition on the silicon-carbon composite layer using a carbon source gas, wherein the carbon source gas is any one or more of acetylene, methane, ethylene, and benzene; and the temperature of the third vapor deposition is 500-1000°C.
Citation Information
Patent Citations
Silicon-carbon negative electrode material, battery negative electrode, battery and preparation method of silicon-carbon negative electrode material
CN117613233A
Method for manufacturing negative electrode for lithium ion secondary battery
JP2017199629A